Robust geometric parameter optimization of a crossed beveloid gear pair with approximate line contact. (February 2022) - Cao, Bing; Li, Guolong; Tao, Yijie; Ran, Quanfu
Highlights: 1.An enhanced geometry design method for crossed beveloid gears was proposed. 2.A robust optimization model of crossed beveloid gears was proposed. 3.The design parameters achieve global optimum under changing misalignment. Abstract: For a crossed beveloid gear pair with approximate line contact, the macroscopic geometric parameter is a dominant factor that affects meshing characteristics. However, geometric parameter design and reliability under misalignment are of great difficulty. To deal with these issues, an enhanced design method for a beveloid gear with approximate line contact is firstly proposed. Based on this, a robust optimization model of geometric parameters for crossed beveloid gear pairs with approximate line contact is developed. Three evaluation items are considered, namely the maximum contact pressure, contact trace offset distance and contact ratio. To reduce the calculation time, the influence coefficient method is applied to calculate the contact pressure. Considering the characteristics of installation deviation uncertainty and distribution, the mean maximum contact pressure, contact trace offset distance and ratio are considered as objective functions, formulated as a robust design optimization problem. Finally, robust optimization of a crossed beveloid gear pair based on a fast elitist nondominated sorting genetic algorithm (NSGA-II) is applied to solve the model to obtain the Pareto front of the macroscopic geometric parameters. A numerical example is provided to demonstrate the effectiveness of the proposed method.